Behavioral Intention and Adoption of Digital Bank Mobile Application Among Housewives Using Mixed Method Approach - Audrey Saudjhana; Herman (Information Technology and Science (ITScience), 2023)
This mixed-method research using PLS-SEM and fsQCA analysis aims to identify the factors that influence the behavioral intention of Indonesian housewives to adopt digital banking applications, particularly by examining the UTAUT2 model's variables. The study found that facilitating conditions, price values, and habits are significant factors that affect the behavioral intention of housewives to use digital banks. Furthermore, the study suggests that paying attention to the factors of effort expectancy, social influence, facilitating conditions, and habits simultaneously is the most effective approach to generating behavioral intention factors in digital bank adoption. The findings have important implications for digital bank companies, the government, financial institutions, and fintech startups. Future research should strive to obtain a more even distribution of respondents from different regions in Indonesia to reduce bias and obtain results that truly represent the conditions of housewives in Indonesia as a whole.